2020
DOI: 10.3389/fmars.2020.00419
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shading and Nutrient Addition on the Microphytobenthos, Macrofauna, and Biogeochemical Properties of Intertidal Flat Sediments

Abstract: Shading, Nutrients and Intertidal Flat Microphytobenthos sediment properties, macrofauna and hence ecosystem functions; but any flow-on effects to the fauna are difficult to predict without further experiments to understand the indirect and direct responses of fauna to changing microphytobenthos and properties of intertidal sediment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…Benthic diatoms have evolved multiple adaptations to cope with the dynamic light conditions and the strong attenuation of incident light by the sediment 22 24 . Many benthic diatoms exhibit maximal growth rates at relatively low photon flux densities (PFD, in this manuscript often simply referred to as “light intensity”) below 50 µE m −2 s −1 , allowing them to thrive in shaded conditions 25 29 . In addition to physiological photoprotection, diatoms from the raphid pennate clade perform behavioural photoprotection by actively migrating through the sediment using their raphe, a longitudinal slit in the frustule equipped with an actin/myosin motility system 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Benthic diatoms have evolved multiple adaptations to cope with the dynamic light conditions and the strong attenuation of incident light by the sediment 22 24 . Many benthic diatoms exhibit maximal growth rates at relatively low photon flux densities (PFD, in this manuscript often simply referred to as “light intensity”) below 50 µE m −2 s −1 , allowing them to thrive in shaded conditions 25 29 . In addition to physiological photoprotection, diatoms from the raphid pennate clade perform behavioural photoprotection by actively migrating through the sediment using their raphe, a longitudinal slit in the frustule equipped with an actin/myosin motility system 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Although we found most of the environmental parameters, we measured were relatively homogenous across the degradation gradient, shading, which obviously declined with a decrease in canopy cover, might have been a key factor responsible for the decline in faunal richness and diversity. Under shadier conditions, due to denser canopies, mangroves produce more leaf litter, cycles more nutrients and maintain higher soil moisture (Tolhurst et al 2020). Heavy shading can significantly modify processes and properties at the sediment-water interface, such as increased carbohydrate accumulation on the burrow surface, which may affect faunal abundance and distribution (Khon et al 2010;Tolhurst et al 2020), as was shown Similar patterns were also observed by Ruwa (1988), who found species diversity greater in moderate shade conditions.…”
Section: Discussionmentioning
confidence: 66%
“…Under shadier conditions, due to denser canopies, mangroves produce more leaf litter, cycles more nutrients and maintain higher soil moisture (Tolhurst et al 2020). Heavy shading can significantly modify processes and properties at the sediment-water interface, such as increased carbohydrate accumulation on the burrow surface, which may affect faunal abundance and distribution (Khon et al 2010;Tolhurst et al 2020), as was shown Similar patterns were also observed by Ruwa (1988), who found species diversity greater in moderate shade conditions.…”
Section: Discussionmentioning
confidence: 66%
“…Examples include long-term moored vessels, docks, wharfs, jetties, and pontoon moorings. Light and shading are known to reduce photosynthesis, growth, and depth distribution of seagrasses [226,227], alter water column and benthic primary production, metabolism and nutrient dynamics [228,229] and benthic community structure and function [230,231]. Studies documenting the effects of shading by dock structures on seagrasses include those by Loflin [232] and Shafer [233].…”
Section: Light Conditionsmentioning
confidence: 99%